Structures and Mechanisms of Community Participation in School Management - Sharma, Tanka Nath (Journal of Education and Research, 2008)
Realizing that community involvement is vital for quality improvement, the government of Nepal decided to transfer the school management authority to the community as a reform measure for school improvement. But the teaching force, one of the important segments of the community is opposing the government’s strategies. This paper attempts to discuss significance and importance of transferring management responsibility to the community from the perspective of theory and practice and highlights the benefits and prerequisites based on the review of international practices. DOI: http://dx.doi.org/10.3126/jer.v1i0.7954 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 72-85